PERAN LEARNING MOTIVATION DALAM MEMEDIASI ACCOUNTING LEARNING ACHIEVEMENT - Kusyanik, Kusyanik; Setiyani, Rediana (Economic Education Analysis Journal, 2018)
Tujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh self-efficacy, teacher competence, dan socio economic status of parents terhadap accounting learning achievement baik secara langsung maupun melalui learning motivation. Populasi penelitian ini adalah seluruh siswa kelas X Akuntansi SMK Negeri 1 Kedung Tahun Ajaran 2017/2018 sejumlah 105 siswa. Sampel yang digunakan dalam penelitian berjumlah 105 siswa dengan menggunakan teknik sampling jenuh. Penelitian ini menggunakan pendekatan kuantitatif. Metode pengumpulan data dengan menggunakan dokumentasi dan kuesioner. Teknik analisis data dengan menggunakan analisis deskriptif dan analisis regresi. Hasil penelitian ini menunjukkan (1) ada pengaruh self-efficacy terhadap accounting learning achievement (2) ada pengaruh teacher competence terhadap accounting learning achievement (3)ada pengaruh soco economic status of parents terhadap accounting learning achievement (4)ada pengaruh learning motivation terhadap accounting learning achievement (5) ada pengaruh self-efficacy terhadap learning motivation (6) ada pengaruh teacher competnece terhadap learning motivation (7) ada pengaruh socio economic status of parents terhadap learning motivation (8) ada pengaruh self-efficacy terhadap accounting learning achievement melalui learning motivation (9) ada pengaruh teacher competence terhadap accounting learning achievement melalui learning motivation (10) ada pengaruh socio economic status of parents terhadap accounting learning achievement melalui learning motivation.Berdasarkan hasil penelitian dapat disimpulkan, bahwa self-efficacy, teacher competence, dan socio economic status of parents berpengaruh terhadap accounting learning achievement baik secara langsung maupun melalui learning motivation. The purpose of this research is to know whether there is influence of self-efficacy, teacher competence, and socio economic status of parents to accounting learning achievement either direcly or through learning motivation as mediation variable. The population of this research is all students of class x SMK Accounting Negeri 1 Kedung in the academic year 2017/2018 in the number of 105 students. The sample used is 105 studnts which a satured sampling. This study uses a quantitative approach. Method of collecting data by using documentation and quesioner. Data analysis techniques using descriptive statistical analysis and regression analysis. The result of this study indicate (1) there is a positive influence of self-efficacy toward accounting learning achievement (2) there is a positive influence of teacher competence toward accounting learning achievement (3) there is a positive influence of socio economic status of parents toward accounting learning achievement (4) there is a positive influence of learning motivation toward accounting learning achievement (5) there is a positive influence of self-efficacy toward learning motivation (6) there is a positive influence of teacher competence toward learning motivation (7) there is a positive influence of socio economic status of parents toward learning motivation (8) there is a positive influence of self-efficacy toward accounting learning achievement through learning motivation (9) there is a positive influence of tecaher competence toward accounting learning achievement through learning motivation (10) there is a positive influence of socio economic status of parents toward accounting learning achievement through learning motivation.